Disturbed dreaming and the instability of sleep: altered nonrapid eye movement sleep microstructure in individuals with frequent nightmares as revealed by the cyclic alternating pattern. - Simor, P; Bódizs, R; Horváth, K; Ferri, R (2013)
STUDY OBJECTIVES: Nightmares are disturbing mental experiences during sleep that usually result in abrupt awakenings. Frequent nightmares are associated with poor subjective sleep quality, and recent polysomnographic data suggest that nightmare sufferers exhibit impaired sleep continuity during nonrapid eye movement (NREM) sleep. Because disrupted sleep might be related to abnormal arousal processes, the goal of this study was to examine polysomnographic arousal-related activities in a group of nightmare sufferers and a healthy control group. DESIGN: Sleep microstructure analysis was carried out by scoring the cyclic alternating pattern (CAP) in NREM sleep and the arousal index in rapid eye movement (REM) sleep on the second night of the polysomnographic examination. SETTING: Hospital-based sleep research laboratory. PARTICIPANTS: There were 17 in the nightmare (NMs) group and 23 in the healthy control (CTLs) group. INTERVENTIONS: N/A. MEASUREMENTS AND RESULTS: The NMs group exhibited reduced amounts of CAP A1 subtype and increased CAP A2 and A3 subtypes, as well as longer duration of CAP A phases in comparison with CTLs. Moreover, these differences remained significant after controlling for the confounding factors of anxious and depressive symptoms. The absolute number and frequency of REM arousals did not differ significantly between the two groups. CONCLUSIONS: The results of our study indicate that NREM sleep microstructure is altered during nonsymptomatic nights of nightmares. Disrupted sleep in the NMs group seems to be related to abnormal arousal processes, specifically an imbalance in sleep-promoting and arousing mechanisms during sleep. CITATION: Simor P; Bódizs R; Horváth K; Ferri R. Disturbed dreaming and the instability of sleep: altered nonrapid eye movement sleep microstructure in individuals with frequent nightmares as revealed by the cyclic alternating pattern. SLEEP 2013;36(3):413-419.